Transactions on Petri Nets and Other Models of Concurrency V - Jensen, Kurt.; Donatelli, Susanna; Kleijn, Jetty; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
These Transactions publish archival papers in the broad area of Petri nets and other models of concurrency, ranging from theoretical work to tool support and industrial applications. ToPNoC issues are published as LNCS volumes, and hence are widely distributed and indexed. This Journal has its own Editorial Board which selects papers based on a rigorous two-stage refereeing process. ToPNoC contains: - Revised versions of a selection of the best papers from workshops and tutorials at the annual Petri net conferences - Special sections/issues within particular subareas (similar to those published in the Advances in Petri Nets series) - Other papers invited for publication in ToPNoC - Papers submitted directly to ToPNoC by their authors The fifth volume of ToPNoC contains revised versions of selected papers from workshops and tutorials held in conjunction with the 31st International Conference on Application and Theory of Petri Nets and Other Models of Concurrency, as well as a contributed paper selected through the regular submission track of ToPNoC. The 12 papers cover a diverse range of topics including model checking and system verification, synthesis, foundational work on specific classes of Petri nets, and innovative applications of Petri nets and other models of concurrency. Thus, this volume gives a good view of ongoing concurrent systems and Petri nets research.
Cycle Structure in SR and DSR Graphs: Implications for Multiple Equilibria and Stable Oscillation in Chemical Reaction Networks -- Modeling and Mining of Learnflows -- Ten Years of Saturation: A Petri Net Perspective -- Refinement and Asynchronous Composition of Modal Petri Nets -- Computing a Hierarchical Static Order for Decision Diagram-Based Representation from P/T Nets -- Bounded Model Checking for Parametric Timed Automata -- Synthesis Problem for Petri Nets with Localities -- A Petri Net Perspective on the Resource Allocation Problem in Software Engineering -- Nets-Within-Nets Paradigm and Grid Computing -- Incremental Process Discovery -- Providing an Agent Flavored Integration for Workflow Management -- A Graphical Approach to Component-Based and Extensible Model Checking Platforms.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information theory; Computer software; Computer simulation; Computer Science; Models and Principles; Theory of Computation; Simulation and Modeling; Software Engineering; Computer Communication Networks; Algorithm Analysis and Problem Complexity